1992
DOI: 10.1111/j.1476-5381.1992.tb09012.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular actions of the κ‐agonist, U‐50,488H, in the absence and presence of opioid receptor blockade

Abstract: 1 The cardiovascular actions of U-50,488H, a K-receptor agonist, were studied in rat isolated perfused hearts, and in anaesthetized rats, over concentrations or doses generally above those required to produce K-receptor-mediated effects. 2 U-50,488H dose-dependently decreased left-ventricular peak systolic pressure and beating rate in vitro and reduced blood pressure and heart rate in vivo. 3 Over the concentration range of 1-30UM in vitro, and the dose-range of 0.5-32,umolkg-1 in vivo, U-50,488H prolonged the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 8 publications
1
13
1
1
Order By: Relevance
“…The rate of intraventricular pressure development (þdP/dt max ) was not affected by PD117,302. These effects are dissimilar to other κ agonists examined in isolated hearts (Pugsley et al, 1992a(Pugsley et al, , 1998. Naloxone had no effect (data not shown).…”
Section: Isolated Heart Studies -Contractility and Ecgcontrasting
confidence: 68%
See 3 more Smart Citations
“…The rate of intraventricular pressure development (þdP/dt max ) was not affected by PD117,302. These effects are dissimilar to other κ agonists examined in isolated hearts (Pugsley et al, 1992a(Pugsley et al, , 1998. Naloxone had no effect (data not shown).…”
Section: Isolated Heart Studies -Contractility and Ecgcontrasting
confidence: 68%
“…In all vehicle control (n¼ 5) and 8.0 mmol/kg naloxone treated (n ¼4, data not shown) animals blood pressure and heart rate were stable over the duration of the drug infusion period, as has been observed with this naloxone dose previously (Pugsley et al, 1992a(Pugsley et al, , 1992b. PD117,302, in the absence and presence of naloxone, produced a marked dose-dependent reduction in both blood pressure and heart rate ( Fig.…”
Section: Blood Pressure Heart Rate and Ecgsupporting
confidence: 52%
See 2 more Smart Citations
“…Several arylbenzacetamide k opioid receptor agonists such as U-50,488H and (7)Cl-977 have been shown to reduce the incidence and severity of ischaemic and electrical arrhythmias in rats (Pugsley et al, 1992a,b). Pugsley et al (1992c) showed that these arylacetamide compounds were still anti-arrhythmic in the presence of speci®c k opioid receptor blockade. Further studies showed that the observed antiarrhythmic ecacy of these compounds was maintained when enantiomeric pairs such as (+) PD 129,290 (which lacks anity for the k receptor) and (7) PD 129,289 (which has high anity for the k receptor) were examined (Pugsley et al, 1993b).…”
Section: Heartmentioning
confidence: 99%